EFEKTIFITAS EMBUNG UNTUK IRIGASI TANAMAN HORTIKULTURA DI CIKAKAK SUKABUMI - Suria Darma Tarigan (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
Dryland farming provides a promising opportunity in increasing agricultural production in rural areas. But, the lack of available water during dry season poses a problem in developing dryland farming. An effective water conservation technique should be developed to alleviate this problem. The use of a small farm reservoir (embung) can be considered as one viable option for such conservation techniques. The purpose of this research was to study the effectivity of small farm reservoirs to supply irrigation water for horticulture commodities. Two different types of small farm reservoir (SFR) were constructed in the micro catchment for the research, i.e. a) SFR built with concrete, b) SFR built without concrete. SFR built with concrete had higher water available for irrigation, which is 34% higher compared to SFR without concrete. In addition, the empirical equation that was used in this research was quite reliable in predicting colected water in the SFRs. Using 80% monthly rain probability, on average one small farm reservoir with dimension 8 m x 2m x 2 m was able to supply irrigation water for 100 m2 horticulture plants for the whole growing period. Keywords: Small farm reservoir, dry season, irrigation, dryland farming.